Starch and β-glucan in a whole-grain-like structural form improve hepatic insulin sensitivity in diet-induced obese mice. Issue 8 (31st July 2019) - Luo, Kaiyun; Wang, Xufeng; Zhang, Genyi
Abstract : WGLSF improves hepatic insulin resistance and glucose homeostasis in diet-induced obese mice. Abstract : Whole-grain food (WGF) is well known for its anti-diabetic effect, and alleviation of obesity-induced insulin resistance (IR) might be one of the underlying mechanisms. In the current study, the effects of starch, as the main component in WGF, and β-glucan in a whole-grain-like structural form (WGLSF) on hepatic IR and glucose homeostasis were investigated using high-fat (HF)-induced obese C57BL/6J mice. After treatment for 8 weeks, the body weight gain and IR of the mice were significantly reduced. The hepatic Akt, the key component in insulin signaling, was activated, and the hepatic expression and protein levels of glucose-6-phosphatase (G-6-P) and phosphoenolpyruvate carboxykinase (PEPCK) were reduced. Moreover, WGLSF effectively reduced the hepatic levels of free fatty acids and the pro-inflammatory cytokines TNF-α, IL-6, and NF-κB. Additionally, the reduced level of the phosphorylated c-Jun-N-terminal kinases (JNK) indicated that WGLSF treatment might inactivate the JNK signaling, leading to improved hepatic IR. These results demonstrated that starch and β-glucan in a whole grain-like structural form have the potential as a dietary strategy to combat obesity-induced hepatic IR for improved health.